Enhancement of Germination and Early Development of Sweet Corn Seeds Using Aerated Priming with KNO3 and Reverse Osmosis Water - Ilham Muhklisin; Putri Santika; Zainani Nur Antika; Sandile Donald Makama (Agroteknika, 2024)
The -sh2, bt2, su1, and se- genes in sweet corn cause faster seed deterioration and a lower germination rate. A potential solution to this issue is seed priming. Priming agents and the solution uptake method are key factors that affect the achievement of seed priming. This study aims to compare the influence of solution uptake methods in sweet corn seed priming as well as investigate the effect of KNO3 on the germination and early development of sweet corn plants. The research was conducted in the Seed processing lab of the Department of Agricultural Production, Politeknik Negeri Jember. The seeds used in this study were sweet corn seeds var. Enno 1401. The study was designed with a completely randomized design (CRD). Seven treatments, namely non-primed, KNO3 spraying, KNO3 soaking, KNO3 aeration, RO water spraying, RO water soaking, and RO water aeration, were observed. Data were analyzed using one-way ANOVA, followed by means analysis using Fisher’s LSD (least significant difference) test at P<0.05. The result showed that aeration priming performed better than spraying and soaking in terms of germination percentage, MGT, and GRI of sweet corn seeds. However, aeration priming with KNO3 gave lower results than RO water in terms of MGT and GRI. On the other hand, aeration priming with KNO3 aeration gave the highest result in dry weight.